Scanner cardiaque pédiatrique dans le diagnostic des cardiopathies congénitales: expérience abidjanaise: Pediatric cardiac computed tomography in the diagnosis of congenital heart disease: abidjan experience. - NCHO MOTTOH Marie-Paule Berdanette; GARBA Idrissa; N’GORAN Yves; ANGORAN Ines; AVOH Ami; DOH Cédric; ALLEKE Samuel Koffi; COULIBALY Ali, (Journal Africain d Imagerie Médicale (J Afr Imag Méd) Journal Officiel de la Société de Radiologie d’Afrique Noire Francophone (SRANF), 2024)
Objective. Since 2008, the French National Authority for Health recommends the use of a cardiac scanner for the diagnosis of congenital heart disease. It helps to confirm and clarify abnormalities that are poorly defined on echocardiography. In developed countries, cardiac CT is a routine examination for the diagnosis of congenital heart disease. In Côte d'Ivoire, its practice is recent. The objective of this study was to describe the techniques and results of paediatric cardiac scans performed in a private facility in Abidjan. Materials and Methods. This was a retrospective descriptive study over a period of 2 months which included all children received at the Rosette clinic for a cardiac scan indicated for the evaluation of congenital heart disease. The examinations were performed under light sedation for children under 7 years of age. Results. Twenty paediatric cardiac scans were performed. The indications for the paediatric cardiac scans were tetralogy of Fallot (15 cases), pulmonary atresia with ventricular septal defect (PAVSD) (2 cases), atrial septal defect (ASD) (1 case), ASD associated with ventricular septal defect (VSD) (1 case) and supravalvular pulmonary stenosis (1 case). In cases of Tetralogy of Fallot and APSO, pulmonary arteries and aorto-pulmonary collaterals were visualised and measured. For the assessment of ASD, an anomalous pulmonary venous return not visualised on echocardiography was found on cardiac computed tomography (CT). In all cases, a malformative CT scan was performed:search for coronary, aortic arch. After the cardiac CT scan, 5 children underwent surgical treatment. There was concordance between the intraoperative and CT diagnoses. Conclusion. In our experience, cardiac CT now represents an important, reliable, minimally invasive, complementary diagnostic tool for the evaluation of congenital heart disease. RÉSUMÉ Objectif. Depuis 2008, la Haute Autorité Sanitaire recommande la réalisation du scanner cardiaque dans le diagnostic des cardiopathies congénitales. Celui-ci aide à confirmer et préciser les anomalies mal définies à l’échocardiographie. Dans les pays développés, le scanner cardiaque est un examen de routine pour le diagnostic des cardiopathies congénitales. En Côte-d’Ivoire, sa pratique est récente. L’objectif de cette étude était de décrire les techniques et résultats des scanners cardiaques pédiatriques réalisés dans une structure privée à Abidjan. Matériels et méthodes. Il s’agissait d’une étude descriptive rétrospective sur une période de 2 mois qui a inclus tous les enfants reçus à la clinique la rosette pour la réalisation d’un scanner cardiaque indiqué pour l’évaluation d’une cardiopathie congénitale. Les examens ont été réalisés sous sédation légère pour les enfants de moins de 7 ans. Résultats. Vingt scanners cardiaques pédiatriques ont été réalisés. Les indications des scanners cardiaques pédiatriques étaient la tétralogie de Fallot (15 cas), l’atrésie pulmonaire à septum ouvert (APSO) (2 cas), la communication inter auriculaire (CIA) (1 cas), la CIA associée à une communication interventriculaire (CIV) (1 cas) et la sténose pulmonaire supra valvulaire (1 cas). Dans les cas de Tétralogie de Fallot et d’APSO, les branches pulmonaires et les collatérales aorto-pulmonaires ont été visualisées et mesurées. Pour le bilan de la CIA, un retour veineux pulmonaire non visualisé à l’échocardiographie a été retrouvé au scanner cardiaque. Dans tous les cas, un bilan tomodensitométrique malformatif était réalisé : recherche d’anomalies coronaires et d’arcs aortiques. Après réalisation du scanner cardiaque, 5 enfants ont bénéficié d’une cure chirurgicale. On notait une concordance entre les diagnostics peropératoires et tomodensitométriques. Conclusion. Dans notre expérience, le scanner cardiaque représente désormais un outil diagnostique complémentaire important, fiable, peu invasif, pour l’évaluation des cardiopathies congénitales.